Intermediate-dose cytarabine plus mitoxantrone versus standard-dose cytarabine plus daunorubicin for acute myeloid leukemia in elderly patients - Röllig, Christoph; Krämer, Alwin (Annals of oncology, 2018)
Background - The combination of intermediate-dose cytarabine plus mitoxantrone (IMA) can induce high complete remission rates with acceptable toxicity in elderly patients with acute myeloid leukemia (AML). We present the final results of a randomized-controlled trial comparing IMA with the standard 7+3 induction regimen consisting of continuous infusion cytarabine plus daunorubicin (DA). - Patients and methods - Patients with newly diagnosed AML>60years were randomized to receive either intermediate-dose cytarabine (1000mg/m2 twice daily on days 1, 3, 5, 7) plus mitoxantrone (10mg/m2 days 1-3) (IMA) or standard induction therapy with cytarabine (100mg/m2 continuously days 1-7) plus daunorubicin (45mg/m2 days 3-5) (DA). Patients in complete remission after DA received intermediate-dose cytarabine plus amsacrine as consolidation treatment, whereas patients after IMA were consolidated with standard-dose cytarabine plus mitoxantrone. - Results - Between February 2005 and October 2009, 485 patients were randomized; 241 for treatment arm DA and 244 for IMA; 76% of patients were >65years. The complete response rate after DA was 39% [95% confidence interval (95% CI): 33-45] versus 55% (95% CI: 49-61) after IMA (odds ratio 1.89, P=0.001). The 6-week early-death rate was 14% in both arms. Relapse-free survival curves were superimposable in the first year, but separated afterwards, resulting in 3-year relapse-free survival rates of 29% versus 14% in the DA versus IMA arms, respectively (P=0.042). The median overall survival was 10months in both arms (P=0.513). - Conclusion - The dose escalation of cytarabine in induction therapy lead to improved remission rates in the elderly AML patients. This did not translate into a survival advantage, most likely due to differences in consolidation treatment. Thus, effective consolidation strategies need to be further explored. In combination with an effective consolidation strategy, the use of intermediate-dose cytarabine in induction may improve curative treatment for elderly AML patients.
Elektronische Reproduktion der Druckausgabe
Available online 7 January 2020
Gesehen am 16.04.2020